ANALISIS KELUARGA BROKEN HOME PADA PERKEMBANGAN BAHASA ANAK - Niam Rohmatullah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2018)
This study aims to increase knowledge or information and at the same time as an example of how the communication experience of broken home children with their environment is in the form of self-concept by analyzing broken home families in children's language. The method used in this study is a qualitative method, which is a method that tends to use analysis. The research subject in this study was conducted on a broken home child. The instruments used in this study were questionnaires and interviews. Finally, it can be concluded that in the results of the study of one of the broken home children in the Bogor area, it was found that the child's attitude could control their emotional and language procedures well